Social vulnerability and cancer risk from air toxins in Louisiana: a spatial analysis of environmental health disparities - Smith, Sadie; Sakhamuri, Sahithya; Guidry, Chloe M.; Mustata Wilson, Gabriela (Frontiers in Public Health, 2025)
IntroductionLouisiana faces significant environmental health challenges due to elevated air toxicity near industrial sites. The state hosts over 300 manufacturing facilities, more than 150 petrochemical plants, and 15 refineries, which, although economically beneficial, pose significant health risks to surrounding communities. Exposure to industrial emissions has been linked to respiratory conditions such as asthma, reproductive disorders, kidney damage, and various cancers. An 85-mile stretch along the Mississippi River, commonly referred to as “Cancer Alley,” has long been associated with elevated cancer rates, particularly among communities with high social vulnerability.MethodsThis study examines the relationship between social vulnerability, cancer incidence, and cancer risk using publicly available datasets, including air toxics data from the United States Environmental Protection Agency (EPA) and cancer incidence rates from the Louisiana Tumor Registry (LTR). Linear regression, interaction analyses, and geographically weighted regression were applied to assess how environmental and socioeconomic factors jointly influence cancer risk.ResultsResults reveal that cancer incidence was associated with elevated air toxins and compounded by social factors such as minority status, low income, and single-parent households. Notably, some regions exhibited a counterintuitive negative association between air toxins and cancer incidence, which may be due to data limitations, including the use of older air quality data, latency in cancer development, or underreporting.DiscussionThese findings underscore the importance of strengthening environmental regulations, real-time air quality monitoring, and community-based public health initiatives to reduce cancer disparities and support affected communities in Louisiana.